A novel human glycoprotein ACA is an upstream regulator of human hematopoiesis - Becker-Kojić, Zorica A.; Ureña-Peralta, J. R.; Saffrich, Rainer; Rodriguez-Jiménez, F. J.; Rubio, M. P.; Rios, P.; Romero, A.; Ho, A. D.; Stojković, Marija (Bulletin of experimental biology and medicine, 2013)
A central issue in stem cell biology is a better understanding of the molecular mechanisms that regulate self-renewal of human hematopoietic stem cells (HSCs). Control of the specific function of HSCs like self-renewal and differentiation might be regulated by a common set of critical genes. However, the regulation among these genes is yet to be elucidated. Here, we show that activation by a novel human GPI-linked glycoprotein ACA at the surface of human peripheral blood progenitor cells induces via PI3K/Akt/mTor/PTEN upregulation of WNT, Notch1, Bmi-1 and HoxB4 genes thus, promoting self-renewal and generation of primitive HSCs. ACA-generated self-renewing cells retained their lympho-myeloid repopulating potential in NOD/SCID mouse xeno-transplantation model with long term functional capacity. We conclude that ACA is an essential regulator of the genes involved in maintaining hematopoiesis and its use in clinical praxis could overcome many of the barriers present so far in transplantation medicine.